Quality of life in patients with pan-cancer undergoing concurrent chemoradiotherapy: a bibliometric analysis (1995-2024) - Shen, Ao; Fan, Pan; Fan, Dingrong; Wang, Yidi; Tang, Kailin; Cai, Ying; Zhou, Hengyu (Frontiers in Oncology, 2025)
BackgroundChemoradiotherapy is a therapeutic approach that prolongs survival but may simultaneously negatively affect the quality of life (QOL) of cancer patients. Current research on quality of life (QOL) in pan-cancer patients undergoing concurrent chemoradiotherapy (CCRT) lacks systematic integration of bibliometric findings with clinical symptom data.MethodsWe retrieved 2762 articles from the Web of Science Core Collections. R-bibliometrix, VOSviewer, and CiteSpace were employed to conduct quantitative analysis and visualize research trends and factors influencing QOL. Complementarily, a cross-sectional study of 117 cervical cancer patients assessed symptom prevalence via CTCAE v5.0, with symptom clusters identified.ResultsThe included articles were published between 1995 and 2024. The results revealed that the United States and China had the largest number of publications worldwide. Van Berge Henegouwen was the most productive author. The institution leading in this field was the University of Toronto. The International Journal of Radiation Oncology - Biology – Physics was the most productive journal. In addition, keywords with high burst strengths in recent years were ‘open label’, ‘predictor’, and ‘preoperative chemoradiotherapy’. Tree-ring map of terms related to QOL was visualized and multiple clusters were found, respectively named as “malnutrition”, “watch and wait”, and so on. Clusters analyses of specific cancers were performed to reveal these unique differences. Finally, among cervical cancer patients, decreased appetite (79.5%), diarrhea (65.8%), and altered taste (59.0%) were the most prevalent symptoms, with three symptom clusters identified.ConclusionMore attention was paid to long-term outcome and patient experience during treatment. Through pan-cancer research and in-depth analysis of specific cancers, we have identified various factors affecting QOL in patients undergoing chemoradiotherapy, including treatment methods, treatment-induced symptoms, psychological factors and so on, enabling us to tailor more personalized treatment plans that improve their overall well-being and enhance QOL during and after treatment.